Crop Switching as Climate Change Adaptation Strategy of Farmers in the Province of Batangas - Resurreccion, Analiza (WIMAYA, 2023)
The geographical scope of the agricultural crops is changing as a result of climate change. In order to reduce the possible negative impacts, notably in developing countries such as the Philippines, this shift requires that crops are switched effectively at community level. In the agricultural communities of the Batangas province, the study identified the social and environmental determinants of crop switching as a locally relevant option for resilience building. One of the key conclusions is that temperature extremes prompted smallholder farmers to abandon crops that cannot tolerate climatic stresses. Introduction of short duration crops and adoption of heat and moisture resistant seed varieties alongside implementation of community-based approaches are suggested to curtail the adverse impacts of climate risks.